INVENTORY OF SPECIES AND HEALTH LEVEL OF SHADE TREES IN PROTOCOL ROAD, PANGKALPINANG CITY - Judianto Sinaga; Robika; Henri (Universitas Medan Area, 2023)
Shade trees have enormous benefits for the urban environment, both ecologically and economically. The level of tree health is important as an ingredient in determining management decisions that will be carried out so that the sustainability of road shade trees remains consistent and maintained. This study aims to inventory shade tree species and analyze the health level of shade trees in the protocol roads of Pangkalpinang City. The research method used the Forest Health Monitoring method. Based on the results of the study, 12 types of shade trees were found in six main streets of Pangkalpinang City with a total of 849 individuals. The most common types of shade trees found were mahogany (Swietenia mahagoni) with 372 individuals (43.82%) and angsana (Pterocarpus indicus) with 296 individuals (34.86%). The health level of shade trees on the Pangkalpinang City protocol road was still dominated by shade trees with a healthy category of 516 individuals (61.36%). Shade trees with light damage category were 175 individuals (20.81%), moderate damage were 66 individuals (7.85%) individuals and severe damage were 84 individuals (9.98%). It can be concluded that the condition of the shade trees in Pangkalpinang City was quite well maintained since the shade trees were still in the healthy category.